2004
DOI: 10.1038/sj.onc.1207721
|View full text |Cite
|
Sign up to set email alerts
|

AKT and mTOR phosphorylation is frequently detected in ovarian cancer and can be targeted to disrupt ovarian tumor cell growth

Abstract: Activation of the PI3K/AKT pathway may contribute to tumorigenesis. AKT mediates survival signals that protect cells from apoptosis and, thus, is a potentially important therapeutic target. To determine the frequency of AKT activation in human ovarian cancer, we screened a tumor tissue microarray with a phospho-specific pan-AKT (Ser473) antibody, which revealed elevated staining in 21 of 31 (68%) ovarian carcinomas. Phospho-AKT staining was associated with that of phospho (active)-mTOR in 27 of 31 (87%) ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
298
6
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(321 citation statements)
references
References 15 publications
16
298
6
1
Order By: Relevance
“…Importantly, compared to the effects of LY294002, a potent PI3-K/AKT signalling pathway inhibitor (Altomare et al, 2004), IC 50 of OSU-03012 is several folds lower in RMS cells. These results indicate that novel OSU-03012 compound may be a more potent inhibitor to PDK-1/AKT pathway than the currently potent inhibitor of PI3-K/AKT, LY294002 to treat childhood RMSs.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, compared to the effects of LY294002, a potent PI3-K/AKT signalling pathway inhibitor (Altomare et al, 2004), IC 50 of OSU-03012 is several folds lower in RMS cells. These results indicate that novel OSU-03012 compound may be a more potent inhibitor to PDK-1/AKT pathway than the currently potent inhibitor of PI3-K/AKT, LY294002 to treat childhood RMSs.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that phosphorylation of Akt and mTOR, an Akt substrate, was frequently detected in ovarian cancer (Altomare et al, 2004). In animal model of ovarian cancer, LY294002, a potent inhibitor of Akt activation, could inhibit cancer growth and ascites formation (Hu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PTEN in ovarian cancer cells suppresses tumor growth (25,26) and its deletion in the mouse ovarian surface epithelium leads to preneoplastic ovarian lesions (27), indicating a strong role for this protein in ovarian cancer etiology. There is ample evidence for the role of the overactivated prosurvival PI3K/Akt pathway in ovarian cancer carcinogenesis (14,15). There is only one study on the effect of sulforaphane on the Akt pathway, which suggests an induction of the pathway in CaCo-2 cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of the Akt pathway has been observed in many cancer types, including breast, endometrial, thyroid cancers, and melanoma (12,13). Components of the PI3K/Akt pathway are frequently overexpressed in ovarian cancer (14,15) and are thought to play major roles in ovarian cancer carcinogenesis. The overexpression of the Akt pathway is frequently associated with poor prognosis and more aggressive phenotype (16).…”
Section: Introductionmentioning
confidence: 99%